Primary and substance-induced psychotic disorders in methamphetamine users - Hides, L.; Dawe, S.; McKetin, Rebecca; Kavanagh, D.; Young, R.; Teesson, M.; Saunders, J. (Elsevier Ireland Ltd, 2015)
This study investigates the rates of primary psychotic disorders (PPD) and substance-induced psychotic disorders (SIPDs) in methamphetamine (MA) users accessing needle and syringe programs (NSPs). The aim was to determine if there are systematic differences in the characteristics of MA users with PPDs and SIPDs compared to those with no psychotic disorder. Participants were 198 MA users reporting use in the previous month. Diagnosis was determined using the Psychiatric Research Interview for DSM-IV Substance and Mental Disorders (PRISM-IV). Current psychiatric symptoms and substance use were also measured. Just over half (n=101) of participants met DSM-IV criteria for a lifetime psychotic disorder, including 81 (80%) with a SIPD and 20 (20%) with a PPD. Those with a younger age of onset of weekly MA use were at increased risk of a lifetime SIPD. A current psychotic disorder was found in 62 (39%), comprising 49 SIPDs (79%) and 13 PPDs (21%). MA users with a current PPD were more likely to have received psychiatric treatment in the past month than those with a current SIPD, despite a similar level of psychotic symptom severity. A high proportion of MA users accessing NSPs have psychotic disorders, the majority of which are substance-induced.